Technological Equipment of Modern Kitchen - Rushana Utkir kizi Quldosheva; Zafarbek Erkinovich Matniyazov; Yashnar Marufovich Mansurov (Genius Journals, 2022)
The article discusses modern trends and trends that are intertwined and create hightech kitchens. The main types of technological equipment with characteristic elements are determined. Such qualities as functionality and ergonomics are emphasized for a comfortable stay in the kitchen space.
Keywords: Automation; Device; Technology; Convenience